Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/md16120461
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Extracted from the New Zealand Undaria pinnatifida—Physicochemical Comparison against Five Other Fucoidans: Unique Low Molecular Weight Fraction Bioactivity in Breast Cancer Cell Lines

Abstract: Fucoidan, the complex fucose-containing sulphated polysaccharide varies considerably in structure, composition, and bioactivity, depending on the source, species, seasonality, and extraction method. In this study, we examined five fucoidans extracted from the same seaweed species Undaria pinnatifida but from different geological locations, and compared them to the laboratory-grade fucoidan from Sigma (S). The five products differed in molecular composition. The amount of over 2 kDa low molecular weight fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…Low‐molecular‐weight fucoidan (LMWF) has been shown to significantly improve disease control rate of metastatic colorectal cancer patients in a clinical trial, combined with chemotherapeutic agents . Some innovative technologies for fucoidan extraction have been developed to promote efficiency to obtain a better yield, with less time, smaller cost, and more environmentally friendly by lowering energy consumption . These include ultrasound‐, microwave‐, and enzyme‐assisted technologies, which have been used in the extraction of fucoidan and other bioactive compounds from ocean algae and seaweed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low‐molecular‐weight fucoidan (LMWF) has been shown to significantly improve disease control rate of metastatic colorectal cancer patients in a clinical trial, combined with chemotherapeutic agents . Some innovative technologies for fucoidan extraction have been developed to promote efficiency to obtain a better yield, with less time, smaller cost, and more environmentally friendly by lowering energy consumption . These include ultrasound‐, microwave‐, and enzyme‐assisted technologies, which have been used in the extraction of fucoidan and other bioactive compounds from ocean algae and seaweed .…”
Section: Discussionmentioning
confidence: 99%
“…39 Some innovative technologies for fucoidan extraction have been developed to promote efficiency to obtain a better yield, with less time, smaller cost, and more environmentally friendly by lowering energy consumption. 44 These include ultrasound-, microwave-, and enzyme-assisted technologies, which have been used in the extraction of fucoidan and other bioactive compounds from ocean algae and seaweed. [41][42][43] In the present work, the ethanol sedimentary method was used, aiming to obtain purer LMWF.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also observed different inhibitory effects against cancer cells from polysaccharides of different molecular weights. For example, Lu et al . reported that low molecular weight fucoidan is more effective than higher molecular form with respect to inhibiting the growth of MDA‐MB‐231 cells, whereas Zhu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also observed different inhibitory effects against cancer cells from polysaccharides of different molecular weights. For example, Lu et al 23 reported that low molecular weight fucoidan is more effective than higher molecular form with respect to inhibiting the growth of MDA-MB-231 cells, whereas Zhu et al 54 observed a stronger antitumor effect for Cordyceps gunnii polysaccharides (over 1000 kDa). Thus, the molecular weight of the polysaccharide appears to be an important factor that dictates its anti-cancer activity, although further studies are needed to ascertain this point.…”
Section: Effect On Porphyrans Of Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation